Adenoid Cystic Carcinoma Mimicking an Oroantral Fistula: A Case Report - Monteiro, Bárbara Vanessa de Brito; Grempel, Rafael Grotta; Gomes, Daliana Queiroga de Castro; Godoy, Gustavo Pina; Miguel, Márcia Cristina da Costa (International Archives of Otorhinolaryngology, 2014)
Introduction Adenoid cystic carcinoma (ACC) is one of the most frequent malignant salivary gland tumors, which commonly affects the minor salivary glands of the mouth and is rare in the nose and paranasal sinuses. In the maxillary sinus, ACC can mimic inflammatory diseases and has a poor prognosis.Objective To report a case of a 50-year-old man with ACC of the maxillary sinus whose clinical findings in the alveolar ridge mimicked an oroantral fistula.Case Report An excisional biopsy was performed and histopathologic analysis revealed ACC. Lung metastases and residual tumor in the maxillary sinus were detected by imaging methods. In view of the poor general health of the patient, no new surgical intervention was performed and he was only treated by radiotherapy and follow-up.Conclusion Although rare in the maxillary sinus, ACC should be included in the differential diagnosis of lesions affecting this site.
Keywords: carcinoma; adenoid cystic; maxillary sinus neoplasms; maxillary sinus